Dynamic Computation of an Innovative Device for Reducing Reaction Torque - Stelica Timofte; Zoltan-Iosif Korka; Attila Gerocs; Andrei Komjaty; Florin Bulzan (Computation)
As is well known, the torque produced by a rotating motor generates an opposite and equal reaction torque in the machine casing that must be transmitted to the base. In many applications, especially when the reaction moment has high values, it is necessary to apply some constructive solutions, which in certain cases are difficult to implement. In this context, the need to reduce the reaction moment from drive motors is a challenging topic which has not been completely exhausted. In this paper, the authors present an original concept of a device which uses the centrifugal force generated by some equidistantly placed weights on a chain drive for reducing the reaction torque of the motor used for driving a rotating tool. The proposed system is capable of producing a supplementary torque which can be added to the driving moment. Due to this fact, by using this system, the power of the driving motor can be decreased, with the consequence of reducing the reaction moment that must be absorbed by the base.